DAMPAK MEDIA SOSIAL TIKTOK TERHADAP PEMBENTUKAN KESADARAN POLITIK PESERTA DIDIK DALAM BERKEWARGANEGARAAN - Kusnadi, Edi; Annisa, Reni Nuraeni (Academy of Education Journal, 2023)
This study aims to determine the impact of tiktok social media on the formation of political awareness of students at SMAN Cimanggung, Sumedang Regency and the content of tiktok social media content as political value content. This research uses a qualitative descriptive approach. The data collection techniques used are through interviews and observations. The results of the study concluded that: the use of tiktok social media is dominated by the millennial generation including students at SMAN Cimanggung, the content in tiktok social media contains political values that are able to shape the attitudes and behavior of students in civic life through the knowledge they get.